Bioakumulasi Logam Berat Merkuri (Hg) Pada Mangrove Jenis Rhizophora Mucronata Di Teluk Kayeli Kabupaten Buru - Ismail, Irwan; Mangesa, Rosita; Irsan, Irsan (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2020)
Kayeli Bay is a water in Buru Regency which has very important value in terms of ecological and economic functions. During its development, the ecosystem in Kayeli Bay bears the burden of pollution, especially heavy metal mercury as a result of the people's gold mining on Buru Island which uses Hg to get pure gold. Hg can accumulate in the environment, especially deposited in the sediments in Kayeli Bay waters. Mangrove plants that generally grow in estuary and coastal environments are a place for sediment accumulation. This plant has the ability to absorb and accumulate heavy metals, one of which is R. mucronata. This study aims to analyze the concentration of heavy metal Hg in mangroves of R. mucronata and sediments, and to analyze the bioaccumulation of heavy metal Hg in R. mucronata in Kayeli Bay, Buru Regency. Samples were taken from 3 stations, namely the Anahoni River Estuary (Station I), the Wailata River Estuary (II Station) and the Waeapo River Estuary (III Station). Each station has 2 sampling points (replicates). Determination of the concentration of Hg metal in the sample using the CV-AAS method. The average value of Hg concentration in the roots was higher than the bark and leaves of the mangrove R. mucronata, but the concentration was lower than the sediment and was still below the critical value of Hg for plants. The average value of sediment Hg concentration is still below the sediment quality standard. In this study, R. mucronata mangroves were excluder and phytostabilized, where there was a limitation on the absorption of heavy metal Hg from water and sediment and the most Hg accumulation was found in the roots. Keywords: Bioaccumulation, Mercury, Rhizophora mucronata, Kayeli Bay